Bentuk Tsumori dan You To Omou yang Menyatakan Maksud: Kajian Struktur - Nova Yulia (Fakultas Bahasa dan Seni UNP, 2010)
This research is emphasized on phrase structure and sentence structure of Tsumori and You To Omou. This research is structural analysis which is conducted to analyze phrase and sentence used Tsoumori and You To Omou that are found in the novel Harry Potta To Kenja No Ishi . This novel is written in Japanese language. It is written by Matsuako Yuuko. The problem that will be analyzed in this research is dealing with phrase structure and sentence structure of Tsumori and You To Omou. The aim of this research is to describe the phrase structure and sentence structure of Tsumori and You To Omou sentence. The method that is used in this analysis is descriptive method by explaining or describing the features of accurate data clearly and in detail. Keyword: Structure, phrase, “tsumori”, “you to omou”